2014
DOI: 10.1149/2.0121410jss
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Referred Binding Energy of the Single 3d, 4d, or 5d Electron in Transition Metal and Lanthanide Impurities in Compounds

Abstract: The vacuum referred binding energy (VRBE) of the single electron in the lowest energy 3d level of Sc 2+ , V 4+ , Cr 5+ , the lowest 4d level of Y 2+ , Zr 3+ , Nb 4+ , Mo 5+ and the lowest 5d level of Ta 4+ , and W 5+ in various compounds are determined by means of the chemical shift model. They will be compared with the VRBE in the already established lowest 3d level of Ti 3+ and the lowest 5d level of Eu 2+ and Ce 3+ . Clear trends with changing charge of the transition metal (TM) cation and with changing pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 165 publications
4
20
0
Order By: Relevance
“…In figure 8 we present the VRBE diagrams stacked next to each other. It shows the top of the valence band, the VRBE in the Eu 2+ 4f 7 ground state and when available in the From a study of Eu in more than 100 different compounds it was found that the VRBE in the lowest 5d state is on average near -1 eV with a tendency to decrease with smaller value for the U-parameter [27]. The level locations for CaO, CaZnOS and CaS in Figure 7 agree with that finding.…”
Section: Discussionsupporting
confidence: 75%
“…In figure 8 we present the VRBE diagrams stacked next to each other. It shows the top of the valence band, the VRBE in the Eu 2+ 4f 7 ground state and when available in the From a study of Eu in more than 100 different compounds it was found that the VRBE in the lowest 5d state is on average near -1 eV with a tendency to decrease with smaller value for the U-parameter [27]. The level locations for CaO, CaZnOS and CaS in Figure 7 agree with that finding.…”
Section: Discussionsupporting
confidence: 75%
“…The difference between these sites should be even greater than is the difference between Y 3 Al 5 O 12 and YAlO 3 that are examples of lattices with high and low crystal field strengths, respectively. They have only a difference of 11% in the YO distances, but, for example, the 3d 1 ground level of Sc 2+ is 1.1 eV closer to the vacuum level in YAlO 3 than Y 3 Al 5 O 12 . Therefore, we can assume that the 3d 1 ground level of Ti Na can be even 2 eV higher (i.e., within the variation limits ±1 eV given in ref.…”
Section: Resultsmentioning
confidence: 67%
“…[170][171][172] Positive correlations showed up, however with an accuracy which is worse than for similar rules for the lanthanides, standard errors being typically of the order of 0.5 eV. Rogers and Dorenbos gathered data to extend the chemical shift model to transition metal ions with a nd 1 ground state configuration (n = 3, 4, 5).…”
Section: Roads For Improvementmentioning
confidence: 99%